Intelligent automated cloth drying system for home application - Aznil, Azmeer Asyraf; Ismail, Nur Asfahani; Norzaliza, Arif Nurhan; Azidin, Azfar Suhail (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
The project is designed to address the inconvenience caused by Malaysia's unpredictable weather, which often disrupts the traditional process of drying clothes. This innovative system integrates IoT technology with a rain sensor, light sensor, and ultrasonic sensor, managed by an ESP32 microcontroller, to ensure efficient and automatic operation. The system activates a motorized mobile roof to protect clothes from rain and extends the hanger when sunlight is detected, providing an effective and user-friendly solution for busy individuals. This invention was driven by the need to provide a cost-effective, automated alternative to conventional cloth-drying methods, offering the dual benefits of convenience and resource optimization. The smart functionality of this project alerts users via the Blynk platform and allows remote control through a smartphone app. The integration of sensors and IoT ensures real-time adaptability to weather changes. The system's impact extends to improving household efficiency, reducing water wastage from re-washing wet clothes, and supporting sustainable living. With its scalable design, low-cost components, and broad appeal, this project holds strong commercialization prospects, particularly in urban and semi-urban markets. It shows a practical solution with significant socio-environmental and economic benefits.